RETRACTED: Upaya Hukum Cessionaris Terhadap Hak Tagih Atas Jaminan Hak Tanggungan Berdasarkan Pengalihan Hutang (Cessie) - Diana Fitriana; Abdul Wahid (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
This article has been retracted at the request of publisher. Reason: This article is virtually identical to the previously published article